PENERAPAN MEREK TERDAFTAR TIDAK DIGUNAKAN (NON-USE MARKS) ANALISIS KASUS ANTARA INTER IKEA SYSTEM BV DAN PT RATANIA KHATULISTIWA PUTUSAN MAHKAMAH AGUNG NO. 264 K/Pdt.Sus-HKI/2015 - Selvy Handoyo; Suyud Margono (Fakultas Hukum Universitas Tarumanagara, 2018)
The development of business competition in the world of trade, making protection of intellectual property rights very important. Especially in the field of brands. Brand is an important thing to use to differentiate between one another by having a certain characteristic. In this paper we will discuss the case of the